Perbandingan Kinerja Database Server MySQL dan SQL Server (Studi Kasus Database Server Politama Surakarta) - Agus Haryawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
There are various kinds of database server application, including MySQL and SQL Server. Each has advantages and disadvantages. Politama server uses SQL Server as its database server application. Program used to access this server is created with desktop applications. Up to this time applications can run smoothly. However, if the server is used to serve as many data requests at the same time, servers are often slow to respond. One solution to overcome this problem is to use an alternative database server application such as MySQL. Before it is implemented, we try to examine the response speed between SQL Server and MySQL. Comparisons were made using two computers with identical specifications. SQL Server and MySQL installed on each computer. Then, an application is created to access both the database server application. The tested instructions are SELECT, INSERT and DELETE. The results showed that MySQL applications provide better performance on all SQL commands. Access time to MySQL 1.85 times faster in SELECT command and 18.25 times faster at INSERT command KRS table records. The difference of access time increase as the number of record increase.